Penerapan Aplikasi Keuangan SI APIK dalam Penyusunan Laporan Keuangan Zoellen Sagela Berdasarkan SAK EMKM - Fidyatul Husna Yunus; Rio Monoarfa; Siti Pratiwi Husain (STIE Amkop Makassar, 2022)
The present research aimed to apply the SI APIK financial application in the preparation of Zoellen Sagela’s financial statement. This research method used a qualitative descriptive research method with primary data sources. At the same time, the data collection method was carried out through observation, interviews, and documentation using the triangulation method as a technique for testing the validity of the data. The research finding denoted that Zoellen Sagela had implemented the SI APIK financial application but had to be discontinued because the manager did not fully understand how to use the application. Meanwhile, after the re-application of the SI APIK financial application in the preparation of financial statements on Zoellen Sagela, the benefits obtained were clearly visible so that it could facilitate Zoellen Sagela in decision-making.